Search for Optimal Parameters for Gas Chromatographic Complex When Determining Sarin in Water Samples by Flame Photometric Detection Method - V. А. Ignatyev; L. V. Petrakova; М. А. Ponsov; А. А. Rodionov (Вестник войск РХБ защиты, 2023)
Sarin is considered to be an instrument for chemical terror by the extremist organizations due to the availability of technologies and components for its production. This fact became evident after the use of sarin by several members of the extremist organization «Aum Shinrikyo» for air infection of the capital`s subway in 1995 in Japan and by ISIL bands in Syria in 2013. Because of its physical and chemical properties, as well as its ability to be dissolved in water in any ratios, sarin can infect water sources for the long period of time. But the sensitivity of flame photometric detectors (FPD) is not always sufficient for the analysis of water samples for the presence of sarin, its precursors and products of destruction, especially in cases of necessity to detect the concentrations less than 0,03 ppm (3×10-5 mg/ml). We have found out that higher sensitivity of the detector can be achieved in case of the increase of the gas carrier (helium) pressure in the injector up to 25 psi, and the temperature – to 250 °C, single-segment temperature rise in the thermostat with a speed of 10 °C/min from 40 °C (1 min) to 280 °C (5 min) at a hydrogen stream in PFD – 75 ml/min, air – 100 ml/min, helium – 60 ml/min. In comparison with the initial method, the offered one is more sensitive in case of sarin concentration in water in the range from 6×10-6 to 1×10-4 mg/ml to 1,7 times. The approbation of the offered optimal parameters was carried out during the gas chromatographic detection of sarin in water samples during the OPCW Proficiency Tests, during the analysis of arbitration samples, during the scientific research and the obtaining of national accreditation of the Laboratory of Chemical Analytical Control of the 27 Scientific Centre of the Minstry of Defence of the Russian Federation. These parameters can be used successfully during the studies of any organophosphorous chemicals by GC analysis with flame photometric detection.